2018
DOI: 10.1088/1751-8121/aae165
|View full text |Cite
|
Sign up to set email alerts
|

Bi-squeezed states arising from pseudo-bosons

Abstract: Extending our previous analysis on bi-coherent states, we introduce here a new class of quantum mechanical vectors, the bi-squeezed states, and we deduce their main mathematical properties. We relate bi-squeezed states to the so-called regular and non regular pseudo-bosons. We show that these two cases are different, from a mathematical point of view. Some physical examples are considered.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Bϕ (2) (J, γ ; x) = i d dγ ϕ (1) for all n 0, with N 1N2 = e −iθ √ π in order to have ϕ 0 , 0 = 1. In [10] we have shown that the bounds in (4.3) (for j = 1) are satisfied and that J min = ∞. Therefore, ϕ (1) (J, γ ; x) and ψ (1) (J, γ ; x) are well defined for all (J, γ ) ∈ R 2 .…”
Section: Gazeau-klauder-like Bicoherent Statesmentioning
confidence: 81%
See 2 more Smart Citations
“…Bϕ (2) (J, γ ; x) = i d dγ ϕ (1) for all n 0, with N 1N2 = e −iθ √ π in order to have ϕ 0 , 0 = 1. In [10] we have shown that the bounds in (4.3) (for j = 1) are satisfied and that J min = ∞. Therefore, ϕ (1) (J, γ ; x) and ψ (1) (J, γ ; x) are well defined for all (J, γ ) ∈ R 2 .…”
Section: Gazeau-klauder-like Bicoherent Statesmentioning
confidence: 81%
“…The commutator between A and B is the difference between the two Hamiltonians: [5,8,9] and references therein, and [10] for a more recent results. We will consider this particular case in Section 5.…”
Section: The General Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we restrict to H 0 , rather than to H ϕ , we get the following result, which relates K ϕ with K −ϕ : 16) for all f (x), g(x) ∈ D(H 0 ). The proof is based on a double integration by part and on the use of the boundary conditions for functions belonging to D(H 0 ), see (2.2).…”
Section: Ii4 the Hamiltoniansmentioning
confidence: 99%
“…Of course, if h = 1 we return to the situation considered in Section II. Hence, to make the situation interesting, in this section we assume h > 1 we consider an Hamiltonian from which a (bi)-squeezed state can be obtained by applying our recurrence procedure, [10].…”
Section: Extended Settingsmentioning
confidence: 99%